The Robust Restriction of Zika Virus by Type-I Interferon in A549 Cells Varies by Viral Lineage and Is Not Determined by IFITM3 - Theodore A. Gobillot; Daryl Humes; Amit Sharma; Caroline Kikawa; Julie Overbaugh (Viruses, 2020)
Type-I interferon (IFN-I) is a major antiviral host response but its impact on Zika virus (ZIKV) replication is not well defined, particularly as it relates to different circulating strains. Interferon stimulated genes (ISGs) that inhibit ZIKV, such as IFITM3, have been identified largely using overexpression studies. Here, we tested whether diverse ZIKV strains differed in their susceptibility to IFN-I-mediated restriction and the contribution of IFITM3 to this restriction. We identified a robust IFN-I-mediated antiviral effect on ZIKV replication (>100-fold reduction) in A549 cells, a commonly used cell line to study ZIKV replication. The extent of inhibition depended on the IFN-I type and the virus strain tested. Viruses from the American pathogenic outbreak were more sensitive to IFNα (p = 0.049) and IFNβ (p = 0.09) than African-lineage strains, which have not been linked to severe pathogenesis. Knocking out IFITM3 expression did not dampen the IFN-I antiviral effect and only high overexpression of IFITM3 led to ZIKV inhibition. Moreover, IFITM3 expression levels in different cells were not associated with IFN-mediated ZIKV inhibition. Taken together, our findings indicate that there is a robust IFN-I-mediated antiviral effect on ZIKV infection, particularly for American viruses, that is not due to IFITM3. A549 cells, which are a commonly used cell line to study ZIKV replication, present an opportunity for the discovery of novel antiviral ISGs against ZIKV.